Social Disorganization, Drug Market Activity, and Neighborhood Violent Crime - Martínez, Ramiro (2008)
Although illicit drug activity occurs within local communities, past quantitative research on drug markets and violent crime in the United States has been conducted mainly at the city level. The authors use neighborhood-level data from the city of Miami to test hypotheses regarding the effect of drug activity and traditional indicators of social disorganization on rates of aggravated assault and robbery. The results show that drug activity has robust effects on violent crime that are independent of other disorganization indicators. The authors also find that drug activity is concentrated in neighborhoods with low rates of immigration, less linguistic isolation and ethnic heterogeneity, and where nondrug accidental deaths are prevalent. The authors find no independent effect of neighborhood racial composition on drug activity or violent crime. The results suggest that future neighborhood-level research on social disorganization and violent crime should devote explicit attention to the disorganizing and violence-producing effects of illicit drug activity.